2005
DOI: 10.1016/j.adolescence.2005.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and drug abuse among young men who have sex with men in New York city: A preliminary epidemiological trajectory

Abstract: The objective of this paper is to profile the role of homelessness in drug and sexual risk in a population of young men who have sex with men (YMSM). Data are from a cross-sectional survey collected between 2001 in New York City (N = 569). With the goal of examining the import of homelessness in increased risk for the onset of drug and sexual risk, we compare and contrast three subgroups: (1) YMSM with no history of homelessness, (2) YMSM with a past history of homelessness but who were not homeless at the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
91
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 34 publications
7
91
2
2
Order By: Relevance
“…Previous research has documented elevated substance use as a coping response to past negative life events and street-survival among both marginally housed YMSM, 10 although our results suggest that ever being kicked out of one's home is a significantly larger predictor of daily marijuana use than past-year homelessness. Substance use among YMSM has also been shown to be associated with experiencing dimensions of minority stress, 27,28 and being kicked out of one's home has been associated with a range of negative health outcomes among sexual minority youth.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Previous research has documented elevated substance use as a coping response to past negative life events and street-survival among both marginally housed YMSM, 10 although our results suggest that ever being kicked out of one's home is a significantly larger predictor of daily marijuana use than past-year homelessness. Substance use among YMSM has also been shown to be associated with experiencing dimensions of minority stress, 27,28 and being kicked out of one's home has been associated with a range of negative health outcomes among sexual minority youth.…”
Section: Discussioncontrasting
confidence: 56%
“…36 Clatts et al examined past stressful experiences in a sample composed of YMSM who were currently homeless, had experienced homelessness but were currently stably housed, and who had never experienced homelessness. 10 All three groups reported high levels of background stressful events, foster care, or involvement in criminal justice systems. Although the majority of homeless and non-homeless youth reported background negative life experiences, and lifetime substance use was pronounced in all three groups, examination of the timing of events across the groups revealed that negative life events occurred prior to the onset of substance use.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This finding has been attributed primarily to past experiences such as sexual abuse and early sexual debut as well as current behaviors such as having multiple sex partners, engaging in sex while under the influence of alcohol and other drugs, exchanging sex for survival needs, and engaging in sex with intravenous drug users. [1,2] One of the National health objectives set forth in Healthy People 2010 is to "promote responsible sexual behaviors, strengthen community capacity, and increase access to quality services to prevent sexually transmitted diseases (STDs) and their complications" [3 p 25].…”
Section: Introductionmentioning
confidence: 99%